Effect of post-operative infections on glioblastoma outcomes - Shah, Zara; Kamran Bakhshi, Saqib; Shamim , Muhammad Shahzad (Journal of the Pakistan Medical Association, 2023)
Glioblastoma multiforme (GBM) is the most aggressive primary brain tumour with a poor prognosis. The risk of developing a post-operative infection after craniotomy is the highest in GBM patients. Historical beliefs suggest that post-operative infections render a survival advantage in GBM patients, however recent clinical neurosurgical reports involving large multicentric patient cohorts do not support this claim. Nonetheless, the relationship has not been extensively studied which poses the need for further large, scaled studies to determine the association between post-operative infections and survival benefit in GBM patients. Keywords: Surgical site infections; glioblastoma surgery; survival time.